Experiential Learning Method in Outingclass Program as Creative and Innovative Learning in PKBM Reksonegaran - Pratiwi, Redna; Fauiziah, Puji Yanti (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2025)
This research employs a qualitative descriptive approach. The aim is to explore the experiential learning method in the Outing Class program as a creative and innovative approach to learning at PKBM Reksonegaran. The research was conducted at PKBM Reksonegaran Yogyakarta, where the informant, a facilitator and administrator, participated. Data collection techniques were employed using observation, interviews, and documentation. The research instrument is based on Kolb's theory of experiential learning. Data analysis techniques use triangulation techniques. The research results found that the Outingclass activity at PKBM Reksonegaran is a creative and innovative program where knowledge is constructed through the transformation of experience. Outing Class provides students with the opportunity to develop and build knowledge through hands-on experiences in the field. To reflect and observe, conceptualize and analyze knowledge in their minds, up to constructing it in the form of a product output resulting from the outing class trip.